CLINICAL MANAGEMENT OF CANINE TRANSMISSIBLE VENEREAL GRANULOMA IN DOGS - Bhatia, Ami; Tank, P H; Kavechiya, V P; Vedpathak, H S; Karle, A S (Indian Journal of Veterinary Sciences and Biotechnology, 2010)
Canine Transmissible Venereal Granuloma (CTVG) is a commonly occurring tumour of dogs affecting both sexes. The pathogenesis, gross and microscopic findings, diagnosis, prognosis and therapies have been reviewed. Six clinical cases of CTVG were treated with vincristine alone and in combination with cryotherapy using liquid nitrogen. Gross findings of small nodule like lesions which bleed was the most consistent clinical finding. Out of these, 5 dogs had an uneventful recovery with complete remission of the tumour gradually whereas there was 1 mortality seen after 10 days of vincristine therapy.